Long Distance Tele-Robotic-Assisted Percutaneous Coronary Intervention: A Report of First-in-Human Experience. (September 2019) - Patel, Tejas M.; Shah, Sanjay C.; Pancholy, Samir B.
Abstract: Background: Robotic-assisted percutaneous coronary intervention (R-PCI) has been successfully employed in the United States since 2011. Performing R-PCI from a remote location has never been reported but if feasible would extend availability of treatment to many patients with coronary artery disease (CAD) who would otherwise go without. Objective: To assess the feasibility of remote tele-R-PCI with the operator 20 miles away from the patients. Methods: Five patients with single, type A coronary artery lesions treatable by PCI consented to participate. The primary endpoint was procedural success with no major adverse cardiac events (MACE) before discharge. Procedural success was defined as achieving < 10% diametric stenosis of the occluded target vessel utilizing tele-R-PCI balloon angioplasty and stent deployment (CorPath GRX®, Corindus Vascular Robotics, USA) without converting to in-lab manual PCI by an on-site standby team. Procedural, angiographic, and safety data were collected as were questionnaire scores from the remote operator evaluating the robot-network composite, image clarity, and overall confidence in the procedure. Results: The primary endpoint was achieved in 100% of patients. No procedural complications or adverse events occurred, and all patients were discharged the following day without MACE. The operator scores were favorable with the operators rating the procedure as equivalent to an in-lab procedure. Conclusions: Performing long distance tele-R-PCI in patients with CAD is feasible with predictably successful outcomes if reliable network connectivity and local cardiac catheterization facilities are available.